Common peritoneal disorders: what the physician should know - Weledji, Elroy Patrick (Gastroenterology Review/Przegląd Gastroenterologiczny, 2023)
Diseases affecting the peritoneum are diverse, ranging from reactive to neoplastic. The abdomen with its peritoneal cavity is part of the body in which diseases are usually thought to be diagnosed and treated almost exclusively by surgeons. However, it is often the general physician who is faced with the initial diagnosis of many of the common diseases of the region, the diagnosis of which may be very difficult. In addition, many chronic lesions that may require surgical treatment may first be seen by the general physician or gastroenterologist. For these reasons, some of the common peritoneal disorders, their presentation, and treatment are reviewed.